Strategic Management of Stakeholders: Theory and Practice - Ackermann, Fran; Eden, C. (Pergamon, 2011)
This article explores how top management teams can increase the robustness of their strategies by attending to important concepts emerging from the stakeholder literature. Analysis of three themes emanating from this literature leads to the development of a method composed of three techniques which elaborates how stakeholder management concepts can be applied in practice. The research, which spanned a 15 year time period, was based on working with 16 top management teams while they were developing their strategies, so that the method e which developed incrementally in response to the teams’ reactions to its utility e was grounded in both theory and practice.